Enhancers reside in a unique epigenetic environment during early zebrafish development. Issue 1 (December 2016) - Kaaij, Lucas; Mokry, Michal; Zhou, Meng; Musheev, Michael; Geeven, Geert; Melquiond, Adrien; de Jesus Domingues, António; de Laat, Wouter; Niehrs, Christof; Smith, Andrew; Ketting, René
Abstract Background Enhancers, not promoters, are the most dynamic in their DNA methylation status throughout development and differentiation. Generally speaking, enhancers that are primed to or actually drive gene expression are characterized by relatively low levels of DNA methylation (hypo-methylation), while inactive enhancers display hyper-methylation of the underlying DNA. The direct functional significance of the DNA methylation state of enhancers is, however, unclear for most loci. Results In contrast to conventional epigenetic interactions at enhancers, we find that DNA methylation status and enhancer activity during early zebrafish development display very unusual correlation characteristics: hypo-methylation is a unique feature of primed enhancers whereas active enhancers are generally hyper-methylated. The hypo-methylated enhancers that we identify (hypo-enhancers) are enriched close to important transcription factors that act later in development. Interestingly, hypo-enhancers are de-methylated shortly before the midblastula transition and reside in a unique epigenetic environment. Finally, we demonstrate that hypo-enhancers do become active at later developmental stages and that they are physically associated with the transcriptional start site of target genes, irrespective of target gene activity. Conclusions We demonstrate that early development in zebrafish embodies a time window characterized by non-canonical DNA methylation–enhancer relationships, including global DNA hypo-methylation of inactive enhancers and DNA hyper-methylation of active enhancers.